Do Surgical Margins Affect Local Recurrence and Survival in Extremity, Nonmetastatic, High‐grade Osteosarcoma?. Issue 3 (March 2016) - Bertrand, Todd E.; Cruz, Alex; Binitie, Odion; Cheong, David; Letson, Douglas G.
Abstract: Background: Long‐term survival for all patients with osteosarcoma using current aggressive adjuvant chemotherapy and surgical resection is between 60% and 70%. In patients who present with nonmetastatic, high‐grade extremity osteosarcoma of bone, limb salvage surgery is favored, when appropriate, over amputation to preserve the limb, because limb salvage may lead to a superior quality of life compared with amputation. However, concern remains that in the attempt to preserve the limb, close or microscopically positive surgical margins may have an adverse effect on event‐free survival. Questions/purposes: (1) Does a positive or close surgical margin increase the likelihood of a local recurrence? (2) Does a positive or close surgical margin adversely affect the development of metastatic disease? (3) What is the relationship of surgical margin on overall survival? Methods: With institutional review board approval, we retrospectively evaluated 241 patients treated at our institution between 1999 and 2011. Exclusion criteria included nonextremity locations, metastatic disease at initial presentation, low‐ or intermediate‐grade osteosarcoma, treatment regimens that did not follow National Comprehensive Cancer Network (NCCN) guidelines, incomplete medical records, and any part of treatment performed outside of Moffitt Cancer Center or All Children's Hospital. Fifty‐one patients were included in the final analysis, of whom 31 (61%) had followup data at a minimum of 2 years or whose clinical status was known but had died before 2 years of followup. Margin status was defined as (1) microscopically positive; (2) negative ≤ 1 mm; and (3) negative > 1 mm. Margin status, histologic response (tumor percent necrosis), type of osteosarcoma, type of surgery, presence of local recurrence, metastatic disease, and overall survival were recorded for each patient. The mean age was 22 years (range, 12‐74 years) and the mean followup was 3 years (range, 0.1‐14 years). Margin status was positive in 10% (five of 51), negative ≤ 1 mm 26% (13 of 51), and negative > 1 mm 65% (33 of 51). Results: Local recurrence was noted to be 14% (seven of 51) at 3.4 years. After controlling for relevant confounding variables, the presence of a positive margin compared with a negative margin > 1 mm was the only independent predictor of local recurrence (hazard ratio [HR], 8.006; 95% confidence interval [CI], 1.314‐48.781; p = 0.0241). At a mean of 3.4 years, 29% (15 of 51) of the patients developed metastatic disease with no difference with the numbers available in the probability of developing metastatic disease among the three margin groups (p = 0.614). Overall survival at 3.8 years was 75% (38 of 51). After controlling for relevant confounding variables, we found that patients with positive margins were more likely to die from disease than those with negative margins (HR, 6.26; 95% CI, 1.50‐26.14; p = 0.0119); no other independent predictors of survival were identified. Conclusions: With the numbers of patients we had, we observed that patients with extremity, nonmetastatic, high‐grade osteosarcoma who had positive margins showed a higher probability of local recurrence in comparison to those with negative surgical margins. Given that positive margins appear to be associated with poorer survival in patients with high‐grade osteosarcoma of the extremities, surgeons should strive to achieve negative margins, but larger studies are needed to confirm these findings. Level of Evidence: Level III, therapeutic study.